Haiti : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criteria; Staff Report; Staff Statement on the Executive Board Discussion; and Statement. (IMF Staff Country Reports; Country Report ;, 2008)
The macroeconomic goals of the first program year were largely met, although growth accelerated somewhat less than expected. Objectives for the second program year (FY2008) are to create conditions for higher growth and consolidate stabilization gains achieved so far. Monetary policy will focus on quantity management, with a market-determined policy interest rate. The authorities plan to further strengthen their monetary policy framework. Macroeconomic policies contained in the program are consistent with the central objective to boost growth while maintaining economic stability.